Analysis of uniparental markers reveals a complex pattern of migration within Sardinia - Renato Robledo; Giuseppe Vona; Emanuele Sanna; Valeria Bachis; Carla Maria Calò (Taylor & Francis Group, 2018)
Background: From the genetic viewpoint, Sardinia is well differentiated from other surrounding populations. In spite of a common ancestral origin, substantial genetic heterogeneity is observed within the island. Matrimonial pattern, as well as past migration movements, may account for the complex genetic structure of Sardinia. Aim: To compare data from uniparental markers in order to highlight the migration pattern of male and female lineages and check their congruence with the demographic data. Subjects and methods: Genomic DNA was obtained from 279 unrelated males selected from three isolated villages and from three open populations representative of North, Central and South Sardinia. The hypervariable region 1 of mtDNA was sequenced and 17 Y-chromosome loci were genotyped. Parameters of within and among populations diversity were calculated and analysis of migration was performed. Results: When analysed as a whole population, demographic data show a balanced movement of males and females in Sardinia, unlike other Italian and European populations. Remarkably, when the island is divided into geographic areas, different migration patterns are clearly recognisable. Whereas North and Central Sardinia populations show a stronger male migration rate, the South Sardinia population shows a stronger female migration rate. Conclusion: Distinct migration patterns of male and female lineages affect the areas investigated differently. These past migration movements are major contributors to the complex genetic structure currently observed in the Sardinian population.